2021
DOI: 10.1186/s40246-020-00299-9
|View full text |Cite
|
Sign up to set email alerts
|

Alu retrotransposons and COVID-19 susceptibility and morbidity

Abstract: SARS-CoV-2 has spread rapidly across the world and is negatively impacting the global human population. COVID-19 patients display a wide variety of symptoms and clinical outcomes, including those attributed to genetic ancestry. Alu retrotransposons have played an important role in human evolution, and their variants influence host response to viral infection. Intronic Alus regulate gene expression through several mechanisms, including both genetic and epigenetic pathways. With respect to SARS-CoV-2, an introni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 87 publications
2
29
0
2
Order By: Relevance
“…Also, high levels and activity of ACE would further increase the activity of the AngII/AT1R pathway. Moreover, advanced age, cardiovascular diseases, hypertension and metabolic diseases such as type 2 diabetes and obesity also lead to further dysfunctions in the renin-angiotensin-aldosterone system (RAAS), likely rendering patients with these underlying comorbidities more susceptible to further repercussions of ACE/ACE2 imbalance ( 7 9 ) and references therein].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, high levels and activity of ACE would further increase the activity of the AngII/AT1R pathway. Moreover, advanced age, cardiovascular diseases, hypertension and metabolic diseases such as type 2 diabetes and obesity also lead to further dysfunctions in the renin-angiotensin-aldosterone system (RAAS), likely rendering patients with these underlying comorbidities more susceptible to further repercussions of ACE/ACE2 imbalance ( 7 9 ) and references therein].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the DD genotype of the ACE I/D polymorphism has been associated to higher levels of serum ACE and higher levels of circulating IL6 in patients with myocardial infarction. In contrast, the II genotype has been associated to lower circulating ACE levels, and robust coagulation, and/or enhanced fibrinolysis ( 7 ). Since some of these processes have been reported to be involved in the pathogenesis of COVID-19, the DD genotype could predispose to complications of COVID-19 due to higher baseline ACE levels and its consequences ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among many Alu elements, the ACE1 polymorphism is a good example of how much research has been done thus far. Despite the fact that the Alu is an intron insertion, it can affect gene expression through several mechanisms, including both genetic and epigenetic pathways [60]. At the molecular level, it has also been reported that the presence of the Alu element within intron 16 probably affects the promoter activity of ACE1, which acts as a transacting repressor for RNA polymerase II activity [61,62].…”
Section: Possible Involvement Of Polymorphic Alu Elements and Their Functional Aspectsmentioning
confidence: 99%
“…And the disease transmission eventually contributed to a pneumonia epidemic outbreak in 2003. 4 , 5 ACE2 receptor is highly expressed in multiple organ systems 6 and plays an essential negative role in the ACE‐angiotensin II (Ang II)‐angiotensin II receptor type 1 (AT1R) pathway called the classical renin‐angiotensin‐aldosterone system (RAAS) axis, whose positive effect can increase sympathetic nervous system tension. 7 …”
Section: Introductionmentioning
confidence: 99%